Friends with boys - Hicks, Faith Erin (First Second, 2015)
After an idyllic childhood of homeschooling with her mother and three older brothers, Maggie enrolls in public high school, where interacting with her peers is complicated by the melancholy ghost that has followed her throughout her entire life.